The Influence of Differentiated Learning Strategies on Motivation and Geography Learning Outcomes - Akhiruddin, Akhiruddin; Bashori, Imam; Pasiamping, Yuniati (AL-ISHLAH: Jurnal Pendidikan, 2024)
The purpose of this study is to ascertain how diverse learning strategies in geography instruction affect the learning outcomes and motivation of SMA Negeri 1 Bunyu geography students. This study employs quantitative techniques and is the kind that has an experimental design with a Nonequivalent Control Group Design, where there is an experimental class that uses differentiated learning strategies, while the control class uses expository learning strategies. The use of this design is based on the problems faced by teachers in the classroom, such as low student motivation to learn, and the strategies used by teachers are not diverse. This design makes it possible to compare different learning strategies between differentiated strategies and expository strategies on student motivation in the classroom. Sixty-three students made up the study's sample, which was selected using a combination of random and probability sampling techniques. SPSS version 25.00 data analysis techniques using the t-test (Independent Sample T-test). With a value of 0.000 0.05, the t-test results showed that using a variety of learning strategies can improve learning outcomes and increase student motivation. Differentiated learning tactics are implemented based on the needs and abilities of students in order to provide an inclusive learning environment. The utilization of various strategies can improve students' academic achievement in addition to encouraging deeper knowledge. The findings of this study show how differentiated instruction can improve students' academic performance and motivation for studying geography.